2021
DOI: 10.20525/ijrbs.v10i7.1457
|View full text |Cite
|
Sign up to set email alerts
|

The influence of workplace happiness and innovative work behavior on job satisfaction mediated by work engagement

Abstract: The purpose of this study is to examine and analyze the influence of workplace happiness and innovative work behavior on job satisfaction mediated by work engagement on employees of a private university in Tenggarong, East Kalimantan during the Covid-19 pandemic. This research is quantitative with a sample of 100 people taken through proportional stratified random sampling. The data analysis technique used is descriptive statistical analysis and structural equation modeling (SEM). The conclusion of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition, a public service motivation theory is discussed by scholars attributable to individuals and organisations that explain public employees' work attitudes, including job satisfaction and organisational commitment (Lu & Chen, 2022). Muafi (2021) confirmed that employees who experience better job satisfaction are likelier to perform better than their dissatisfied counterparts. Therefore, women public employees' job satisfaction is crucial for an organisation to pay attention to, especially during implementing of the Work From Home (WFH) policy in Malaysia.…”
Section: Job Satisfactionmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, a public service motivation theory is discussed by scholars attributable to individuals and organisations that explain public employees' work attitudes, including job satisfaction and organisational commitment (Lu & Chen, 2022). Muafi (2021) confirmed that employees who experience better job satisfaction are likelier to perform better than their dissatisfied counterparts. Therefore, women public employees' job satisfaction is crucial for an organisation to pay attention to, especially during implementing of the Work From Home (WFH) policy in Malaysia.…”
Section: Job Satisfactionmentioning
confidence: 96%
“…Job satisfaction can be understood as a positive feeling and pleasurable emotion that an employee attains from work done or from what the employee experienced (Batura et al, 2016). It is closely related to one's happiness and good feeling when doing a job (Muafi, 2021). Similarly, job dissatisfaction means one's negative and unpleasurable emotions that an employee experienced in their position (Pakistan et al, 2020).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…An employee has no desire to act and do something contrary to the existing code of ethics in the company. Rosdaniati and Muafi's (2021) study emphasized the importance of job satisfaction in enhancing innovative work behavior. They suggest that companies should regularly assess and evaluate their employees' job satisfaction.…”
Section: The Influence Of Job Satisfaction On Innovative Work Behaviormentioning
confidence: 99%